IMPLEMENTASI PENDIDIKAN KARAKTER RELIGIUS SEBAGAI PONDASI MENGHADAPI TANTANGAN ABAD KE 21 DI SDN PANIMBANGJAYA 5 - Fijriyati; Zerri Rahman Hakim; Istinganatul Ngulwiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was conducted at SDN Panimbangjaya 5, Pandeglang Regency for data collection, findings and results. In an effort to face the challenges of the 21st century, the existence of religious character education is needed to overcome the moral crisis and rampant forms of misappropriation. The implementation of religious character education is a foundation in filtering values that tend to be morally opposite. This study aims to discuss the urgency of implementing religious character education for elementary school-age children in facing the challenges of the 21st century. The results showed that the implementation of religious character was carried out by religious habituation of students through religious activities. Religious activities carried out at SDN Panimbangajaya 5 are the recitation of the short letter Juz'amma before learning, Friday Takwa with the habituation of Dhuha Prayers in congregation, Shalawat together, recitation of Asmaul Husna, and Islamic Spirituality by Da'i/Da'iyah from students in rotation every week. In the implementation of religious character education, of course, there are supporting and inhibiting factors encountered. The supporting factors; (1) full support from the school (2) student enthusiasm (3) parental support. The inhibiting factors; (1) the diversity of student backgrounds (2) limited time and resources (3) inadequate facilities and infrastructure (4) adaptation to the times. Challenges in the implementation of education.